Communicating about obesity and weight-related topics with children with a physical disability and their families: spina bifida as an example. Issue 8 (10th April 2017) - McPherson, Amy C.; Swift, Judy A.; Peters, Michelle; Lyons, Julia; Joy Knibbe, Tara; Church, Paige; Chen, Lorry; Farrell, Renée M.; Willem Gorter, Jan
Abstract: Purpose : The purpose of this study was to explore the experiences of children with spina bifida (SB), their families and healthcare professionals (HCPs) when discussing weight-related topics. Method : In-depth qualitative interviews were conducted with HCPs from Canadian outpatient SB clinics ( n  = 13), children aged 6–18 years with SB ( n  = 17) and their parents ( n  = 20). Data were analyzed using a phenomenological approach within an interpretative paradigm. Results : Many HCPs were not confident talking about weight, concerned that they would damage relationships with children and families. Parents wanted routine weight surveillance, but were worried about their children's self-esteem if their weight was discussed. They wanted HCPs to acknowledge the challenges of weight management in children with a physical disability and provide specialized solutions. Children wanted a positively framed and tailored approach to weight discussions, although this had generally not been their experience. Conclusions : Stakeholders describe therapeutic relationships that are currently disconnected around the issue of weight and obesity. However, children, parents and HCPs all believed that discussing this topic was critical. Positively framed, strengths-based and tailored approaches to weight-related discussions are warranted. Implications for Rehabilitation: Rates of overweight and obesity in children and youth with physical disabilities are substantially higher than their typically developing peers. Healthcare professionals, children with physical disabilities and families often find weight-related discussions challenging and disconnected. Weight-related discussions should be tailored to the child and family's circumstances and priorities. Positively framed and strengths-based approaches to weight-related discussions are warranted.